ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA DRIVER OJEK ONLINE DI KOMUNITAS LASKAR AMPERA TAHUN 2022 - Andira Aulia Rachmawati (2022)
Online transportation is very helpful for the community in various activities. Someone who works in online transportation has flexible working hours and continues to deal with traffic jams, so they are prone to occupational fatigue. This study aimed to determine whether there is a relationship between work stress and workload with work fatigue on online motorcycle taxi drivers in the Laskar Ampera community in 2022. The research used quantitative analysis with a cross-sectional study design. The sample of this study consisted of 123 online motorcycle taxi drivers in the Laskar Ampera community. This sample was obtained using purposive sampling. Chi-square test is used to determine the relationship between variables. This study shows that the variables related to work fatigue are workload with p-value (0.038) and work stress with p-value (0.001), while the variables that are not related to work fatigue are age (p-value 1000), sex (p-value 0.787), length of service (p-value 0.554), and years of service (p-value 0.137). There is a relationship between workload and work stress with work fatigue, online motorcycle taxi drivers must be be able to manage stress and reducing workload in order to reduce the risk of work fatigue, because if the workload increases and work stress increases, work fatigue will increase. Keywords: Work fatigue, taxis online, and work stress.